Analisis Dukungan Organisasional Persepsian Dan Employee Engagement Terhadap Kinerja Karyawan: Kepuasan Kerja Sebagai Pemediasi - YUNI SISWANTI YUNI; Krisnandini Wahyu Pratiwi (Jurnal Manajemen dan Keuangan, 2020)
This study aims to analyze the effect of perceived organizational support (POS) and employee engagement on performance and the role of job satisfaction in mediating the effect of perceived organizational support (POS) and employee engagement on performance. The population in this study were permanent employees at PT. Solusi Bangun Indonesia Tbk. The research method used was a survey and a sample size of 185 employees. The research instrument adopted from previous research. Retrieval of data by means of questionnaires and interviews. Validity and reliability tests show all questionnaire items are valid and reliable. To test H1 and H2 with simple regression, H3 and H4 test with Baron and Kenny regression model. The results of hypothesis testing show that: (1) perceived organizational support has a significant effect on employee performance, (2) employee engagement has a significant effect on employee performance, (3) job satisfaction partially mediates the effect of perceived organizational support on employee performance, and (4) job satisfaction does not mediate the effect of Employee engagement on employee performance.